Determinar el grado de eficacia de la colocación de malla (TOT), en pacientes con incontinencia urinaria del Área de Ginecoobstetricia del Hospital Manuel Ygnacio Monteros de la ciudad de Loja, periodo julio 2012 - junio 2013. - Aguirre Rueda, Diego Hernán (2013)
Urinary incontinence is a widespread problem among middle-aged women , for correction techniques have been described in recent years with different success rates and complications. Our goal is to determine the effectiveness TOT placement in obstetrics and gynecology patients with urinary incontinence Manuel Ygnacio Monteros Hospital of the city of Loja, period July 2012 to June 2013.  At month were interviewed , in 56 clients who met the inclusion criteria after reviewing their medical records pre and post-surgery, it was determined that 47 users ( 83.9 % ) the degree of efficacy was high ( without loss of any kind ), being the great multiparous the most affected with 37 cases ( 66.1 % ), with an average age that borders the 54 years were also included previous major gynecological surgeries , making them the previous colpoperineoplasty back with 7 cases ( 12.5 % ), plus the accompanying gynecological pathology in 28 patients ( 50 % ) for grade III cystocele and rectocele . Was obtained satisfaction of 46 cases (82%). The main complication was pain in 9 users (16.1 %), along with the side effect of urinary function, corresponding to dysuria in 5 cases (8.9%), which are easy to handle . In conclusion it is determined that the surgical technique, TOT placement has a high degree of efficiency, with a high rate of satisfaction.